Corporate social responsibility and firm financial performance: Comparison analyses across industries and CSR categories. Issue 3 (8th August 2017) - Feng, Mingming; Wang, Xiaodan; Kreuze, Jerry Glenn
Abstract : Purpose: Despite the intensive research on corporate social responsibility (CSR) and firm financial performance, little is known about how the linkage between CSR and firm financial performance is heterogeneous across industries and how the performance implications are differentiated among specific categories of CSR activities. The purpose of this paper is to explore how the association between a firm's engagement in CSR and firm financial performance is heterogeneous across industries and CSR categories. Design/methodology/approach: Using a sample of 17, 083 firm-year observations representing 1, 877 firms from the largest 3, 000 US companies during years 1991 and 2011, the authors compare the association between CSR and firm financial performance across ten industry sectors defined by Global Industry Classification Standard and across the four CSR categories classified by Mandl and Dorr (2007). Findings: The authors find that the association between the overall CSR activities and firm performance is heterogeneous across industries. CSR has significant positive implications for firms from most, but not all, industries. Comparing the performance implication of CSR practices targeting different stakeholder groups, the empirical results indicate that different types of CSR have different influences on financial performance of firms from different industry sectors. Research limitations/implications: This study provides new angles for managers in maximizing firm performance through CSR activities and suggests an important and interesting direction for researchers who engage in CSR research. Due to its heterogeneous nature, the CSR-performance relationship needs to be examined more specifically – across industries and different CSR categories. Findings from studies incorporating both company industrial sector and CSR categories would provide more meaningful and practical implications for managers. Practical implications: This study provides important managerial implications. First, to maximize firm performance through CSR activities, managers must interpret the linkage between CSR and firm financial performance from the perspective of a specific industrial sector and acknowledge the importance of CSR practices across different CSR categories. Second, the findings suggest that CSR practices aiming at different stakeholder groups generate different financial returns in different industries. Firms engage in CSR to satisfy different stakeholder groups. When budgets are tight, managers may give higher priority to the CSR practices that have stronger effects on firm financial performance. Originality/value: This study advances our understanding of the CSR-financial performance relationship by exploring its heterogeneous nature across industry sectors and across specific categories. To obtain the biggest gain from CSR spending, managers must have a good understanding how a specific CSR category can contribute to the financial performance of their particular company in their particular industry.